Research Update: The nitride route to ammonia fertilizers: decoupling food and fossil fuel - Pfromm, Peter H. (My University, 2016)
A new three-year project at Kansas State University, sponsored by the U.S. Department of Energy, Basic Energy Sciences (U.S. DOE Office of Science, Award No. DE-SC0016453, "Step Catalysis to Synthesize Fossil-Free Ammonia at Atmospheric Pressure"), with $598,866 pursues ammonia for fertilizers produced from renewable resources with a new simple and rugged process. The team of Principal Investigator Dr. Peter Pfromm (Chemical Engineering), and co-Principal Investigators Dr.'s Bin Liu (Chemical Engineering) and Viktor Chikan (Chemistry) and their graduate students are investigating forming metal nitrides from metal alloy nanoparticles to activate nitrogen from air, and then synthesizing ammonia in a second step, all at atmospheric pressure and moderate temperatures. The recent precipitous decline in the cost of renewable electricity allows the needed hydrogen to be made by electrolysis of water so that the entire process is essentially fossil fuel free, economically competitive with fossil fuel based ammonia, and proceeds under conditions that will allow down-scaling and operation on stranded or intermittent renewable electricity.
Keywords: Research Update; U.S. Department of Energy; Ammonia; Fertilizers; Renewable Resources; Fossil-Free Ammonia